SWOT-ANALYSIS OF OUTSOURCING OF ACCOUNTING SERVICES - ADASIUK, ILONA; MARTYNIUK, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article based on SWOT-analysis of outsourcing of accounting services. Accounting services can be improved if you can work on your strengths, as well as correct the weaknesses of the company or area where you lose points. SWOT-analysis is considered as a tool of strategic management to determine the feasibility of using accounting outsourcing as a way to optimize the enterprise. SWOT consists mainly of two main parts: strengths and weaknesses, which will indicate the internal aspect, and threats and opportunities related to external factors for the company (but those that are present in the environment). In essence, we test the effectiveness of the accounting services provided by the contractors that your business provides against this background.With this analysis, the firm can understand the problems, ie where they lack work and why, because these are periods during the year when work becomes fragile. Why this happens is best analyzed because of it. A set of business goals are things that outsourcing companies need to invest because simple marketing is not enough. The analysis of advantages and disadvantages of accounting outsourcing is carried out and the necessity of SWOT-analysis of potential risks and advantages of using perspectives of accounting outsourcing is emphasized.The internal and external environment was analyzed using an extended SWOT analysis model from the standpoint of strengths and weaknesses, opportunities and expected threats. Based on the results of the SWOT-analysis, a matrix has been formed that will allow predicting threats and potential opportunities at the stage of planning the use or refusal to use accounting outsourcing services.
Keywords: outsourcing; accounting; accounting functions; competitiveness; SWOT analysis; weaknesses; strengths; threats; opportunities